Susan swan and the female grotesque - Suzana Bornéo Funck (Ilha do Desterro)
Introduced to readers as “the tallest woman freelance writer in Canada”, Susan Swan belongs to a generation of writers whose experimental, innovative fiction has proved vital in the contemporary project of de/re/constructing narrative practice. Her 1983 novel The Biggest Modern Woman of the World constitutes an excellent example of what critic Linda Hutcheon has termed “historiographic metafiction”—”fiction that is intensely, self-reflexively art, but is also grounded in historical, social, and political realities” (Canadian 13). As a conscious engagement with social and historical contexts, such fiction aims at destabilizing and subverting accepted patterns of belief by reconceptualizing and narrating possible subjectivities. By means of intertextuality, especially parody, it engages in an ideological critique in terms of both sexual and national politics.